Pengaruh Variasi Bentuk Permukaan Forging Sambungan Las Gesek Rotary Terhadap Kekuatan Tarik Baja Mild Steel - Partomuan, Putra; Yohanes, Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Along with the times, welding technology has undergone many developments. The new methods in the process of connecting material are an evidence of developments in welding technology, one of which is friction welding. The friction welding is a welding without using electrode, that the connection between the two materials of welding is obtained a homogeneous connection. The friction welding can also be used to connect cylindrical material or non-cylindrical material. This study aims to analyze the effect of variations in the forging surface (chamfer angle) on tensile strength of welded joints of the rotary friction welding using mild steel. In this study used the mild steel material, which a diameter of 8 mm shaped cylindrical. The cylindrical with a length of chamfer 2 mm and diameter forging of 4 mm by variation of the angle of 300, 450, and 600 were investigated in this research. Then, the rotational speed was 3800 rpm, friction pressure of 4 bars, and the forging pressure of 6 bars were applied in this research. Result showed work piece surface conditions (chamfer angle) affect the value of the tensile strength of steel mild steel. Specimens with diameter forging of 4 mm have a tensile strength value of an average of 424.63 N/mm2, 530.79 N/mm2 and 563.81 N/mm2. The specimen with a chamfer length of 2 mm has an average tensile strength of 585.04 N/mm2, 537.86 N/mm2 and 450.58 N/mm2.Keywords: Friction Welding, Mild Steel, Chamfer Angle, Maximum Tensile Strength.